2019
DOI: 10.1108/lht-01-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of the papers on urban education

Abstract: Purpose The purpose of this paper is to identify the papers published on urban education and analyze the characteristics of these papers to contribute to the urban education research over the recent years. Design/methodology/approach Researchers generated a comprehensive list of the articles published between 2010 and 2017 in the field of “urban education” by searching the Social Sciences Citation Index database, using the keywords of “urban” and “education.” As an additional criterion, all the articles publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
(26 reference statements)
1
15
0
1
Order By: Relevance
“…Arokiasamy and Tat (2020) conducted an empirical study on 369 full-time academic employees of higher-education institutions in Malaysia. The results showed that transformational leaders were able to create a workplace spirit that increased employees' ability to engage in learning (Chen et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Arokiasamy and Tat (2020) conducted an empirical study on 369 full-time academic employees of higher-education institutions in Malaysia. The results showed that transformational leaders were able to create a workplace spirit that increased employees' ability to engage in learning (Chen et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Also, the intermediary role of entrepreneurial self-efficacy was verified through data quantification. It is hoped to provide some data references for the improvement of the entrepreneurial performance of start-ups in the context of entrepreneurship education (Chen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The FTA method is further optimized, that is, fuzzy mathematics is introduced to describe the uncertainties of occurrence probability of the bottom event that may cause college classroom teaching failure. Then, the probability interval of teaching failure is simulated by the double-layer MCM (Chen et al, 2019 ). Finally, the probability interval of college classroom teaching effect is evaluated quantitatively.…”
Section: Discussionmentioning
confidence: 99%